Implementation of Legal Protection Regarding Copyright for Works of Painting - Adeline Pricilla Putri; Ismayani Ismayani; Taufika Hidayati (SEAN Institute, 2026)
In Indonesia, works of art are protected by Law Number 28 of 2014 concerning Copyright (Law 28/2014), which regulates the exclusive rights of creators, including moral rights and economic rights. This protection applies automatically without the need for registration, although registration with the Directorate General of Intellectual Property (DJKI) remains important as proof of legal ownership. This study aims to analyze the legal protection policy for paintings in Indonesia. Paintings are a form of creative expression with high economic and cultural value. However, paintings are also vulnerable to copyright infringement, necessitating effective legal protection. This study uses a normative legal research method with a legal policy analysis approach. The data used in this study are secondary data obtained from legal sources, such as Law Number 28 of 2014 concerning Copyright, government regulations, and court decisions. The results indicate that the legal protection policy for paintings in Indonesia is regulated by Law Number 28 of 2014 concerning Copyright. This law provides legal protection to creators of works of art regarding their economic and moral rights. However, the lack of awareness and knowledge about copyright among artists and the general public are some of the factors that contribute to the ineffectiveness of this policy. Furthermore, the costs of copyright registration are excessively high. Based on the research findings, the author recommends several things: (1) increasing awareness and knowledge about copyright among artists and the general public through education and training; (2) promptly registering works of art with the Directorate General of Intellectual Property Rights (DJKI) to ensure stronger legal protection and evidence in the event of a copyright dispute; (3) including watermarks on works of art as identification to prevent plagiarism. Therefore, this research is expected to contribute to improving legal protection regarding copyright for works of art in Indonesia.